The Strategy for Distributing Zakat Funds in Improving the Welfare of Mustahik by BAZNAS of Lima Puluh Kota Regency for the Community of Nagari Galugua, Kapur IX District - Meinora, Sinta; Joni, Yefri; Rahman, Ali; Rahmi, Rahmi (Yayasan Rahmat Islamiyah, 2026)
This study aims to determine Baznas Lima Puluh Kota Regency's Efforts in Distributing Zakat Funds Evenly in Nagari Galugua, Kapur IX District. This study uses a qualitative descriptive research type that produces descriptive data in the form of words and the use of theoretical foundations so that the focus of the research is in accordance with field facts. Data collection methods are by interview, direct observation in the field, and documentation. The results of the study from Baznas' efforts in distributing zakat funds evenly in Nagari Galugua face internal and external challenges. For internal, Baznas faces limited human resources who are certified and qualified as Amil Zakat. While external, the geographical conditions of Nagari Galugua are remote and difficult to reach, making it difficult for Baznas officers to access.